IMPACT OF COVID-19 CARONAVIRUS ON POVERTY IN PAKISTAN: A CASE STUDY OF SINDH - DR. Faiz Muhammad Shaikh; Ali Raza Memon; Kashaf Shaikh (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2020)
The current research investigated the COVID-19 is spreadvigorously in China, USA, France, Italy, Germany, andEuropean countries and Iran Pakistan being as a neighborcountry of china & Iran One was for the incoming Pakistanifrom various countries, such as Iran, China, Afghanistan, andIndia. The other was arranged inside various hospitals forCOVID-19 positive cases. As hundreds and thousands ofPakistani were in Iran for religious purposes, they were. Mostof the students and businessmen, inside China, were notallowed to come back. Handling of large scale influx from Iranwas the main problem. Out of the total COVID-19 cases, 78percent of cases were reported from visitors coming from Iran.Pakistan announced the closure of all schools, colleges &universities with a partial lockdown across the country formajor cities